Respuesta :

msm555

Answer:

[tex] (f + g)(x) = -4\sqrt[3]{5x} [/tex]

Step-by-step explanation:

2)

To find [tex] (f + g)(x) [/tex], we add [tex] f(x) [/tex] and [tex] g(x) [/tex].

Given:

  • [tex] f(x) = -\sqrt[3]{5x} [/tex]
  • [tex] g(x) = -3\sqrt[3]{5x} [/tex]

We perform [tex] (f + g)(x) [/tex] as follows:

[tex] (f + g)(x) = f(x) + g(x) [/tex]

[tex] (f + g)(x) = (-\sqrt[3]{5x}) + (-3\sqrt[3]{5x}) [/tex]

[tex] (f + g)(x) = -\sqrt[3]{5x} - 3\sqrt[3]{5x} [/tex]

To combine these terms, notice that they share the same radical term. So we can add them directly:

[tex] (f + g)(x) = (-1 - 3)\sqrt[3]{5x} [/tex]

[tex] (f + g)(x) = -4\sqrt[3]{5x} [/tex]

So, [tex] (f + g)(x) = -4\sqrt[3]{5x} [/tex].

ACCESS MORE